The Jewish Kulturbund in Bavaria, 1934-1938 art and Jewish self-representation under National Socialism - Smith, Dana 1987- (Queen Mary University of London, 2015)
This thesis has two foci: the development of a National Socialist anti-Jewish cultural policy and the processes of internal Jewish community cultural self-representations. At the most basic level it is an organisational history of the Jewish Kulturbund in Bavaria between 1934 and 1938. Ultimately, however, the thesis is about the people: the artists, how they employed certain mediums for specific uses and how these events were received. The Kulturbund was the lone state approved Jewish cultural organisation in Nazi Germany; it was, in other words, the only public space for Jewish cultural performance and consumption. Activity began in Berlin in the summer of 1933 and expanded to cities, towns and villages throughout the country. Unlike the majority of these early branches, however, the Jewish Kulturbund in Bavaria developed independently of Berlin’s main offices. Bavarians maintained autonomous control of their cultural league until the autumn of 1935. Organised Bavarian Jewish cultural life was ‘liquidated’ upon official state orders after 9 November 1938. This thesis analyses the Kulturbund programme as an internal projection of willed identity for Bavarian Jews. Kulturbund events – particularly in the early seasons when National Socialist censorship was ill-‐defined and haphazardly enforced – reflected the ways its membership chose to stage their own understandings of what it meant, to them, to be 'Jewish'. It was a process of dissimilation and internal community building that helped its membership navigate their experiences of political persecution and social flux. What developed in the Bavarian programme from February 1934 until November 1938 was a representation of ‘Jewishness’ that was self-described as both religious and heritage-based with a regional bent.